An Analysis of Teacher Questions and Student Responses in the English Teaching-Learning Process - Susantara, I Putu Anom Didik; Myartawan, I Putu Ngurah Wage (Journal of Education Reseach and Evaluation, 2020)
This study aimed to analyze the types of teacher questions, the purposes of the teacher in asking questions, and student responses to the teacher questions in the English classroom. The current study was a case study. The study involved an English teacher and seventh grade students of SMP Negeri 4 Singaraja. The data were collected through observation and interview guide. The data analysis technique used was descriptive and interactive data analysis. The result of the analysis showed that the teacher more frequently asked convergent and display questions rather than divergent and referential questions. Procedural questions were also found. The teacher’s questions served several purposes such as to develop students' interests and curiosity, to examine students' knowledge, and to diagnose student difficulties in the learning process. Discussions and suggestions are further presented in this paper.